Effect of Soil Extracts on Ability of Clinical Isolates of Pseudomonas aeruginosa and Staphylococcus aureus to Produce Biofilm in vitro - Farah Mohommed Saleh (World Journal of Experimental Biosciences, 2017)
In present study the effect of soil extracts of different types of soil on ability of two clinical isolates, Pseudomonas aeruginosa and Staphylococcus aureus to form biofilm. The extract of soil was done by using sterile phosphate buffer saline and analyzed by Fourier Transform Infrared Spectroscopic (FTIR). Spectrophotometric method was used to check ability of the studied isolated bacteria to form biofilm on polystyrene microtiter plates. The data of FTIR showed very little difference was observed among extracts of three types of soil (soil contaminated with hydrocarbons; garden soil collected from gardens of al-jadrea, Baghdad and containers soil), but the highest difference was observed in the extract obtained from peat moss clay soil. The results of current study showed that the extracts of soil contaminated with hydrocarbons and garden soil increased the biofilm that form by P. aeruginosa (P
Keywords: Biofilm, Pseudomonas aeruginosa, Soil extracts, Staphylococcus aureus.